Segmen Berita Feature Pada Program Berita Jawa Tengah Hari Ini di TVRI Stasiun Jawa Tengah - Abimanyu Satriyo Wicaksono; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Television is still one of the media with the highest number of access currently in Indonesia. The presentation of shows that are increasingly diverse and entertaining has made many television stations now compete with each other. No exception in presenting news broadcasts. One of the television stations, namely TVRI Stasiun Jawa Tengah, tries to present a broadcast in the form of a feature news segment as one of the steps to support the rebranding that is being carried out. The implementation of rebranding targeting the millennial generation certainly makes TVRI Central Java Station have to provide interesting news shows. One of them is the feature news segment which was produced by the Communication Science Team of Diponegoro University. The feature news segment is produced according to the interests of the millennial generation, which provides information, entertainment, and education about tourism, culinary, and communities, especially in areas around Central Java. During the production process the roles of producer, reporter, scriptwriter, cameraman, voice-over, and editor are very important, in order to present complete information supported by delivery and attractive visuals. Of course it is not easy to do each of these roles. Idea selection, crew distribution, news angle determination, shooting techniques, and editing in accordance with the script and standard operating procedures must be done maximally in order to produce news worthy of broadcast on television. The feature news segment airs on the Central Java program Today on TVRI Central Java Station at 16.00-17.00 WIB every Monday to Thursday with a total of 48 news segments. Aired from 26 July 2020 to 2 November 2020.